Resource Factor Analysis with Performance of Ponkesdes Nurses in Mojokerto District - Tio Nanda Saputra; Faisal Ibnu; Duwi Basuki (STIKes Patria Husada Blitar, 2022)
Ponkesdes is a pioneer in healthy development and plays an important role in the implementation of the Healthy Indonesia program. It is critical to examine the performance of nurses to maintain and improve the quality of health services at ponkesdes. The good performance of Ponkesdes nurses is a bridge in answer the guarantee of the quality of health services provide to patients both sick and healthy. In this case, the author tries to analyze organizational factors with the performance of ponkesdes. The research method is quantitative, the type of research use is a correlations study and uses a correlational cross-sectional design. The population in this study were nurses who worked in Ponkesdes. The population in this study was taken from 19 sub-districts. There are 27 Puskesmas with 211 Ponkesdes Nurses. Sampling in this study was carried out using the probability sampling method through a simple random sampling technique, from 211 Ponkesdes taken randomly, 170 Ponkesdes nurses were taken. The Analyzed research uses univariate (a form of categorical data, which is carried out on careful variables), bivariate (Chi-Square), and Multivariate (regresi logistic tests). The results of the binary logistic regression test obtained a significant value (p = 0.00; = 0.05) which means that there is a significant relationship between human resources, rewards, leadership, job design, and job structure with the performance of Ponkesdes nurses in Mojokerto Regency. And the results of the logistic regression test, the factor most related to the performance of the ponkesdes nurses in Mojokerto Regency was leadership with the value of Exp (B) = 15.379. The results of the study can be used by ponkesdes nurses in conducting nursing interventions to improve the quality of nursing services through organizational management.